ANALISIS KEPUASAN MASYARAKAT ATAS KUALITAS PELAYANAN KEPOLISIAN PADA KANTOR DIREKTORAT INTELIJEN KEAMANAN POLISI DAERAH BENGKULU - Hendra Kusuma; Merri Anitasari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2014)
Hendra Kusuma, Merri Anitasari; Purpose of this study was to determine the intelligence directorate office services at the regional police security Bengkulu. Method data collecting the used is questionnaire. Analysis method the used is Index Satisfaction of Society. Pursuant to result of data analysis and research about service analysis at intelligence directorate office services at the regional police security Bengkulu, hence can be pulled an conclusion that average value per highest service element is clarity care workers of service given by intelligence directorate office services at the regional police security Bengkulu that is with value of unsure service equal to 2,77 and average value per lowest service element that is at certainty of expense equal to 2,41. Value of IKM at intelligence directorate office services at the regional police security Bengkulu equal to 63,9 meaning that service unit performance at intelligence directorate office services at the regional police security Bengkulu is " goodness", because the value reside in among 62,51 - 81,25 residing in a quality of service of B (good).Key words:Service Quality